The influence of the educators' brain dominance on their teaching strategies : the case of elementary teachers - Kamel, Noha (Beirut Notre Dame University.Humanities, 2010)
Teachers may prefer to use one brain hemisphere over the other. The purpose of the thesis was to study the influence of brain hemisphere dominance on teaching strategies. The participants were sixty elementary teachers purposively selected from English and French speaking schools in the Kesserwan, Jbeil, and Metn areas in Lebanon. It was hypothesized that teachers with the right brain dominance preference would significantly include more whole brain teaching strategies in their lesson plans than those of left brain dominance. The data was quantitatively analyzed using chi-square to determine the teaching strategies used by the participants in their lesson plans. The chi-square test showed significant difference between the left brain and the right brain teachers when choosing their preferred teaching strategies; the research hypothesis was accepted fo X (2, N=60) = 5.789,p<.05. The data was also qualitatively analyzed by tabulating the answers received from the in-depth interview. The in-depth interview gave evidence and support to the research hypothesis. It was conclued that teachers should try to integrate strategies that trigger both brain hemispheres even though they and their students have brain dominance. Students should be provided with a rich environment that helps connect and develop the neurons, and this environment could be provided by teachers using whole brain strategies. Limitations of the study and suggestions for future research were also discussed.
: Mémoire
Keywords: Cycle primaire; Elementary Education; Performance professionnel; Professional performance